A wealth-requirement axiomatization of riskiness - Sergiu Hart; Dean P. Foster (Theoretical Economics, 2013)
We provide an axiomatic characterization of the measure of riskiness of gambles (risky assets) introduced by Foster and Hart (2009). The axioms are based on the concept of "wealth requirement."
Keywords: D81; G00; G32; 330; Riskiness; gamble; risky asset; reserve; wealth